Biomechanical evaluation of multiple pelvic screws and multirod construct for the augmentation of lumbosacral junction in long spinal fusion surgery - Yang, Honghao; Pan, Aixing; Hai, Yong; Cheng, Fengqi; Ding, Hongtao; Liu, Yuzeng (Frontiers in Bioengineering and Biotechnology, 2023)
Background Posterior long spinal fusion was the common procedure for adult spinal deformity (ASD). The incidence of pseudoarthrosis and implant failure is high in long spinal fusion extending to lumbosacral junction (LSJ). To address this problem, advanced SPF technique by multiple pelvic screws or multirod construct has been recommended. This study compared the biomechanical performance of combining multiple pelvic screws and multirod construct to other advanced SPF constructs for the augmentation of LSJ in long spinal fusion surgery through finite element (FE) analysis. Methods An intact lumbopelvic FE model based on computed tomography images of a healthy adult male volunteer was constructed and validated. The intact model was modified to develop five instrumented models, all of which had bilateral pedicle screw (PS) fixation from L1 to S1 with posterior lumbar interbody fusion and different SPF constructs, including No-SPF, bilateral single S2-alar-iliac (S2AI) screw and single rod (SS-SR), bilateral multiple S2AI screws and single rod (MS-SR), bilateral single S2AI screw and multiple rods (SS-MR), and bilateral multiple S2AI screws and multiple rods (MS-MR). The range of motion (ROM) and stress on instrumentation, cages, sacrum, and S1 superior endplate (SEP) in flexion (FL), extension (EX), lateral bending (LB), and axial rotation (AR) were compared among models. Results Compared with intact model and No-SPF, the ROM of global lumbopelvis, LSJ, and sacroiliac joint (SIJ) was decreased in SS-SR, MS-SR, SS-MR, and MS-MR in all directions. Compared with SS-SR, the ROM of global lumbopelvis and LSJ of MS-SR, SS-MR, and MS-MR further decreased, while the ROM of SIJ was only decreased in MS-SR and MS-MR. The stress on instrumentation, cages, S1-SEP, and sacrum decreased in SS-SR, compared with no-SPF. Compared with SS-SR, the stress in EL and AR further decreased in SS-MR and MS-MR. The most significantly decreased ROM and stress were observed in MS-MR. Conclusion Both multiple pelvic screws and multirod construct could increase the mechanical stability of LSJ and reduce stress on instrumentation, cages, S1-SEP, and sacrum. The MS-MR construct was the most adequate to reduce the risk of lumbosacral pseudarthrosis, implant failure, and sacrum fracture.